O dilema de arrendar ou fornecer cana-de-açúcar: Uma alternativa para geração de renda nos assentamentos da reforma agrária - Amorim, Fernando Rodrigues de; Patino, Marco Túlio Ospina; Lucente, Adriano dos Reis [UNESP] (My University, 2016)
Sugar cane production by settlers of agrarian reform is an alternative of income but presents the dilemma of leasing the land or providing the production to the factories. This study analyzed the feasibility of production under the rental system and compared with the system of own production. The method was based on literature review, descriptive analysis of data, and comparison of economic feasibility of the two systems. It was found a break even point for groups of six settlers or 30 hectares and the own production system being 12.52% more profitable to settlers, however, outsourcing the necessary practices of cultivation.
The dilemma of lease or providing cane sugar: An alternative for generation of income in settlements of land reform
Keywords: Economic feasibility analysis; Settlement land reform; Sugar cane